Nouvelle réglementation juridique de la planification du territoire en Pologne (Contemporary Central & East European Law, 1985)
The article analysis the Law of the 19th July 1985 on Spatial Planning which introduced changes necessary after the reform of administrative division of the state and the introduction of the communes. Furthermore, more and more intensive industrialisation resulted in adjusting the local plans to the planned localisation of new investments. Also, the growing society needed more residential space what was not possible to achieve without the changing of the existing spatial plans.It is highlighted that the aim underlying the introduction of new law was to guarantee the coordination of general and local interest, by introducing the measures allowing to take into account social, natural and economic conditions of each region.The plans are adopted on several levels (national, regional and local). The national one covers the general provisions that takes into consideration the aims of the country development, the environmental protection concerns, protection of natural resources and the cultural heritage, the need for constant development of social and technical facilities for residential needs, sustainable development (taking into account both industrial and agricultural needs) and security and defence issues.  There are some imprecisions with defining the regional level. Accordingly to new administrative division of the country, it should mean the voivodeships, what is highlighted in the article. Nevertheless, the plans on this level should emphasis the development of voivodeship, without neglecting its influence on the neighbouring voivoideships. The local plans should take into consideration the needs of the local community. The law predicts also the spatial plans for the special functionality terrains (mines, agglomerations, national natural parks).In the further part of the article, there is a brief review over the process of adoption of the abovementioned plans. They are prepared by the Planning Commission within the Council of Ministers and broadly consulted. The representatives of the administration bodies, the social element and the representatives of the councils of people are also engaged in the process. The further obligations linked to the adoption of these plans are analysed in the latter part of the article.The specific procedure  for the localisation of investments is analysed in the last part of the article, it should have the form of the administrative act and is litigable before the Administrative Court. What’s more, it cannot change the provisions of the existing plans. What is more, in order to obtain consolidation with these plans, it need to be consulted with Planning Commission within the Council of Ministers if it regards the investment of national importance, and with local or regional authorities if the investment is of local importance. Moreover, it should be also consulted with the Environment and Water Resources Protection Office and the General Sanitary Inspection.The transition period provisions are of great practical value and regulate that all of the ongoing processes are conducted due to the old procedures. The new plans should be elaborated till the 31st December 1986 (it can be prolonged till the 31st December 1988).